ANALISIS FAKTOR RISIKO KONDISI FISIK RUMAH TERHADAP PENYAKIT TB PARU DI WILAYAH KERJA PUSKESMAS BARENGKRAJAN KABUPATEN SIDOARJO TAHUN 2020 - Marita Elvina U; Narwati .; Putri Arida Ipmawati (GEMA LINGKUNGAN KESEHATAN, 2022)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. The high rate of pulmonary TB in the working area of the Barengkrajan Health Center can be caused by the physical conditions of the house such as the type of wall, type of floor, ventilation area, lighting, temperature, humidity, and house occupancy density that does not meet the requirements of 17.9% (2,386 houses). The purpose of the study was to analyze the risk factors for the physical condition of the house on pulmonary TB in the Barengkrajan Health Center Work Area.The method used is observational with an analytical approach and case control design. The sample size is 32 cases and 32 controls using simple random sampling method. Data were analyzed using odds ratio.The results showed that the OR for the type of wall was 0.873, the OR for the type of floor was 1.696, the OR for the ventilation area was 1.457, the OR for lighting was 2.647, the OR for humidity was 1.64, the OR for the density of occupancy was 2.896, and the OR for conditions was large. physical house is 2,707.The risk factors for the occurrence of pulmonary TB are the physical condition of the house, type of floor, lighting, humidity, and residential density of the house, and those that are not risk factors for pulmonary TB are the type of wall, ventilation area, and temperature.